Why Teaching Ethics to AI Practitioners Is Important - Goldsmith, Judy; Burton, Emanuelle (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
We argue that it is crucial to the future of AI that our students be trained in multiple complementary modes of ethical reasoning, so that they may make ethical design and implementation choices, ethical career decisions, and that their software will be programmed to take into account the complexities of acting ethically in the world.